Percepções de mulheres acerca da saúde mental: estudo de caso em um assentamento rural - Fabris, Juliana (2024)
The territory responds to and is characterized by the individuals and experiences lived within it. In this sense, the territory and the processes that involve the subjects' struggle for land include occupations, camps and settlements. In these spaces, women assume an important role by taking responsibility for family and domestic care, in addition to actively collaborating in supporting the family. Considering women have an important social, cultural, community and family role in this scenario, the need to discuss their relationships with the health process and mental illness is understood. This study aimed to understand the perceptions of women living in a rural settlement about mental health and what care actions they carry out for this purpose. As for the method, it is a case study with a qualitative approach, exploratory and descriptive in nature. The research was carried out with women aged 18 or over, residing in Assentamento 16 de Março, municipality of Pontão, Rio Grande do Sul. Data generation took place between the months of June and October 2023, through the sources: documentary analysis, individual interview and workshop. Data analysis was carried out through thematic content analysis, followed by data triangulation. This research observed the ethical aspects recommended for research with human beings. Cardiovascular, respiratory, integumentary, skeletal/muscular and mental health problems were identified. The women presented a positive view in reference to ‘being a woman and living in the settlement’ and the work carried out in this space, but without dismissing their challenges. Women's perceptions of health and mental health are identified, as well as the elements that promote health and mental health developed in the settlement. With the development of this research, it is expected to increase interest in studies in rural areas and in settlements, as well as provide visibility of the significance of women and the peasant population who occupy these spaces, mainly related to knowledge regarding mental health.